Pengaruh Lingkungan Islami Terhadap Perkembangan Kreativitas Siswa di Seklolah SMP Islam Terpadu Bina Insan Cemerlang Bondowoso - Azzam Taufiqy Nur Santoso; Bahar Agus Setiawan; Hairul Huda (SS&H: Studies in Social Sciences and Humanities, 2025)
Humans grow and develop in their environment. The environment is inseparable from human life. The environment always encompasses humans from time to time, so there is a reciprocal relationship between humans and the environment where the environment affects humans and vice versa humans also affect the environment. The environment also affects the development of students' creativity. The approach carried out in this study is a quantitative approach that focuses on the influence of the Islamic environment on the development of student creativity at the Bina Insan Cemerlang Integrated Islamic Junior High School Bondowos. This type of research uses a survey method. The research instruments that will be used by the researcher in this study are observation sheets that contain statements related to the variables of the Islamic education environment and questionnaires that contain statements related to the variables of Islamic character. The questionnaire to be used is first tested for validity and reliability with the help of the SPSS version 25.0 program. Instruments that have passed the validity and reliability tests can be used to collect data. The results of the data analysis show that the hypothesis proposed can be concluded, namely that there is a negative relationship between the free variable (X), namely the Islamic environment, and the bound variable (Y), namely the creativity of students at the Bina Insan Cemerlang Integrated Islamic Junior High School, with a correlation/relationship value (R) of 0.089. From these outputs, a determination coefficient (R Square) of 0.008 was obtained, which means that the influence of the free variable (Islamic environment) on the bound variable (Student Creativity) was 8%. Thus, to answer the researcher's question with the answer "there is an influence of the Islamic Environment on Student Creativity at the Bina Insan Cemerlang Integrated Islamic Junior High School, Bondowoso".